2015
DOI: 10.1212/wnl.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

Time from convulsive status epilepticus onset to anticonvulsant administration in children

Abstract: Objective: To describe the time elapsed from onset of pediatric convulsive status epilepticus (SE) to administration of antiepileptic drug (AED).Methods: This was a prospective observational cohort study performed from June 2011 to June 2013. Pediatric patients (1 month-21 years) with convulsive SE were enrolled. In order to study timing of AED administration during all stages of SE, we restricted our study population to patients who failed 2 or more AED classes or needed continuous infusions to terminate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
138
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 33 publications
3
138
0
Order By: Relevance
“…Delays in time to treatment are independently associated with worse outcomes in the short term (higher mortality, higher need for continuous infusions, longer convulsive duration, and more frequent hypotension) 1, 2, 3, 33, 82, 83. Families and caregivers play a crucial role, as timely treatment is often possible if families and caregivers administer a rescue medication at home and quickly call emergency services 84, 85, 86. However, a survey of 100 families of patients with epilepsy showed that 87% had a rescue medication prescription, but only 61% of them reported receiving training on how to use it 86, 87.…”
Section: Factors Affecting Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Delays in time to treatment are independently associated with worse outcomes in the short term (higher mortality, higher need for continuous infusions, longer convulsive duration, and more frequent hypotension) 1, 2, 3, 33, 82, 83. Families and caregivers play a crucial role, as timely treatment is often possible if families and caregivers administer a rescue medication at home and quickly call emergency services 84, 85, 86. However, a survey of 100 families of patients with epilepsy showed that 87% had a rescue medication prescription, but only 61% of them reported receiving training on how to use it 86, 87.…”
Section: Factors Affecting Outcomementioning
confidence: 99%
“…However, a survey of 100 families of patients with epilepsy showed that 87% had a rescue medication prescription, but only 61% of them reported receiving training on how to use it 86, 87. Furthermore, a study showed that only 37.5% of patients received prehospital treatment 85. Improving these factors could impact short‐term outcomes.…”
Section: Factors Affecting Outcomementioning
confidence: 99%
“…Both adults [13][14][15][16][17] and children [17][18][19][20] receive antiepileptic drugs (AEDs) later than recommended by most SE guidelines. [21][22][23] Most episodes of pediatric SE occur in children with no history of seizures.…”
mentioning
confidence: 99%
“…[21][22][23] Most episodes of pediatric SE occur in children with no history of seizures. 1,19 However, there are no data on whether having a history of seizures or SE results in more timely treatment-including initial abortive medication and escalation of therapies-and better outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation